The Balancing Between The Principles Of Justice, Legal Certainty, And Expediency In The Implementation Of Auction Execution In The Settlement Of Civil Cases - Erlan Jaya Putra; Siti Rodiah; Djuhaendah Hasan (Magister Kenotariatan Universitas Pasundan, 2022)
The ultimate goal of the law enforcement process is that the law guarantees the implementation of equal justice and protection for human dignity, order, peace, and legal certainty under the provisions of the law. Three principles must receive professional attention, although it is challenging to do in practice. Therefore, the Judge must make every effort so that every decision rendered contains the three principles that are the basis and purpose of the law. The research method used in this research is analytical descriptive data obtained from secondary legal sources. The data obtained from field studies and document studies are then analyzed in a qualitative juridical manner. After the data has been collected, it is poured into a logical and systematic description without using mathematical formulas. The purpose of a court is to obtain a judgment and decision-making that knows the actuality of the case. As well as the legal rules governing it that will be applied, both legal authorities wrote in legislation and unwritten law, and to analyze the application of the three principles in the judgment and decision making. The results prove that judgment and decision-making are unrest and unsortable in life without these three principles, especially for justice seekers. Furthermore, the research results show that in applying legal certainty, whatever happens, the rules are so and must be obeyed or implemented. The application of justice is fair if it can provide balanced treatment between rights and obligations. While utilization means that the law exists for humans, then implementing the law or law enforcement must benefit society.